A lattice discrete particle model to simulate the viscoelastic behaviour of macro – synthetic fibre reinforced concrete. (9th August 2021) - Del Prete, C.; Boumakis, I.; Wan-Wendner, R.; Vorel, J.; Buratti, N.; Mazzotti, C.
Highlights: Fibre reinforced concretes long term performance is a still open topic. The viscoelasticity of polymeric fibres in concretes cannot be neglected. Experimental test procedure for time dependent strains of FRCs are not standardized. Viscoelasticity of FRCs must be considered in numerical models. The number of fibers is important in FRC short and long term response. Abstract: Given the growth in structural applications of fibre reinforced concretes (FRCs), the characterization of their mechanical performance, and the formulation of predictive models are necessary. When dealing with FRCs long-term behaviour, concrete creep deformations can be predicted but the fiber–matrix interaction produces new effects, i.e. non-linear bond behaviour, creep of polymeric fibres, affecting the long-term performance of cracked elements. The present paper introduces a novel computational framework simulating the long-term behaviour of cracked FRC elements with polymeric fibres, adopting the Lattice Discrete Particle Model (LDPM) theory. The innovative contributions of the research concern the inclusion of the fibre viscoelastic behaviour.